2020
DOI: 10.1021/acs.jced.0c00323
|View full text |Cite
|
Sign up to set email alerts
|

Robust Ultramicroporous Metal–Organic Framework with Rich Hydroxyl-Decorated Channel Walls for Highly Selective Noble Gas Separation

Abstract: Separation of a gas mixture achieved by the vacuum swing adsorption (VSA) technology is considered as an efficient and energy-saving method for Xe/Kr mixtures, but developing efficient and stable adsorbents remains challenging. Herein, we report an ultramicroporous metal–organic framework, namely, MIL-120 with a suitable pore size (5.4 Å × 4.7 Å), rich hydroxyl-decorated sites, and ultrahigh stability, which is capable of highly selective adsorption of xenon from krypton. Specifically, MIL-120 exhibits an exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…These values were slightly higher than those previously reported, which may be attributed to the sample washing step using high temperature methanol. 44 The pore size distribution was evaluated using the Horvath-Kawazoe model (Figure 2b) and the calculated pore size (4.8 Å) was consistent with the results obtained from the crystal structure (5.4 × 4.7 Å). 40 From a practical point of view, the pH value of the initial solution and thermal stability are two key metrics for evaluating the adsorbent.…”
Section: Theoretical Calculationssupporting
confidence: 77%
“…These values were slightly higher than those previously reported, which may be attributed to the sample washing step using high temperature methanol. 44 The pore size distribution was evaluated using the Horvath-Kawazoe model (Figure 2b) and the calculated pore size (4.8 Å) was consistent with the results obtained from the crystal structure (5.4 × 4.7 Å). 40 From a practical point of view, the pH value of the initial solution and thermal stability are two key metrics for evaluating the adsorbent.…”
Section: Theoretical Calculationssupporting
confidence: 77%
“…Several very recent experimental reports used the strategy outlined above to improve separation properties, as well as tuning the chemical nature of the organic linkers. Tao et al 66 68 showed that a strategy of decoration of the internal pore surface with polar groups could fine-tune the separation properties in ultramicroporous MOFs: they modified the MIL-120 material by introducing hydroxyl groups, increasing the Xe/Kr selectivity.…”
Section: Recently-proposed Candidates For Separationmentioning
confidence: 99%
“…S1 † that MIL-120 and MIL-118 have been successfully synthesized. 24,25 Fig. S2 † shows that both the as-prepared samples have a rodlike morphology, however, the size of MIL-118 is much Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The observed characteristic peaks of Al-BTEC at 9°, 13°a nd 20°and the peaks at 9°, 18°, 25°, 43°and 44°are corresponding to the characteristic peaks of MIL-120 and MIL-118, respectively, indicating that the obtained Al-BTEC is a mixture of two MOF structures. 24,25 The characteristic peak at 25°of Al@C is assigned to the (220) crystal plane of γ-Al 2 O 3 . It can also be seen that the characteristic peaks of Al 2 O 3 disappear after treatment with a NaOH solution, and only the peaks of porous carbon remain in SPC.…”
Section: Resultsmentioning
confidence: 99%